Pounded plants on cotton: Methods, outcomes, and colorfastness of post-treatments - Haar, Sherry J.; Doty, Kelsie (My University, 2017)
Plant pounding is the transfer of plant pigment onto textiles through the mechanical force of hammering. The resulting image can mimic the original petal or leaf. A challenge can be poor colorfastness. Even though this is a popular technique with several writings on the process, we could find no research examining colorfastness properties. Thus, we examined orange cosmos petals and purple sweet potato leaf pounded onto cotton print cloth for colorfastness to laundering and light exposure following AATCC procedures. Fabric was scoured and mordanted with aluminum acetate. Following pounding, three post-treatments were applied, including steam, a sodium silicate fixative, and a cationic dye fixative. CIELab color coordinates were taken with a spectrocolorimeter. Cosmos exposed to laundering and light had considerable color change with steam having the most similar color ratings and appearance to its standard. Purple sweet potato leaves had noticeable color change following laundering, with steam retaining original color and imagery best. Conversely, colorfastness to light was poor for all treatments. Overall, a steam treatment is recommended to assist with color and image retention for pounded plants onto cotton fabric that is scoured and mordanted with aluminum acetate.
Citation: Haar, S., & Doty, K. (2017). Pounded plants on cotton: Methods, outcomes, and colorfastness of post-treatments. Peer reviewed Proceedings Paper published in The 10th International Shibori Symposium Official Proceedings 2016, Oaxaca, MX, Luximon A. (Ed.), pp. 59-66. Berkeley, CA: World Shibori Network. ISBN: 978-1-5323-3312-5. Available: https://10thiss.files.wordpress.com/2016/03/10iss-press-kit_proceedings.pdf
Keywords: Sweet potato leaf; Cosmos; Hammering; Steam; Fixing agents